On the problem of attribute selection for software cost estimation: Input backward elimination using artificial neural networks - Papatheocharous, Efi; Andreou, Andreas S. (My University, 2010)
Many parameters affect the cost evolution of software projects. In the area of software cost estimation and project management the main challenge is to understand and quantify the effect of these parameters, or 'cost drivers', on the effort expended to develop software systems. This paper aims at investigating the effect of cost attributes on software development effort using empirical databases of completed projects and building Artificial Neural Network (ANN) models to predict effort. Prediction performance of various ANN models with different combinations of inputs is assessed in an attempt to reduce the models' input dimensions. The latter is performed by using one of the most popular saliency measures of network weights, namely Garson's Algorithm. The proposed methodology provides an insight on the interpretation of ANN which may be used for capturing nonlinear interactions between variables in complex software engineering environments.
Keywords: Artificial neural network; Software project; Artificial neural network models; Attribute selection; Backward elimination; Complex software; Connection weights; Cost drivers; Garson's algorithm; Input dimensions; Network weights; Nonlinear interactions; Prediction performance; Saliency measure; Software cost estimations; Software development effort; Software systems; Algorithms; Costs; Estimation; Project management; Software design; Neural networks